2022
DOI: 10.3390/cancers14112726
|View full text |Cite
|
Sign up to set email alerts
|

PET-CT in Clinical Adult Oncology—V. Head and Neck and Neuro Oncology

Abstract: PET-CT is an advanced imaging modality with many oncologic applications, including staging, assessment of response to therapy, restaging, and longitudinal surveillance for recurrence. The goal of this series of six review articles is to provide practical information to providers and imaging professionals regarding the best use of PET-CT for specific oncologic indications, and the potential pitfalls and nuances that characterize these applications. In addition, key tumor-specific clinical information and repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 143 publications
0
6
0
1
Order By: Relevance
“…In routine practice, the analysis of 18 F-FDG PET/CT images of the head and neck region is challenging [27,28]. The intricate anatomical composition of the head and neck region, its proximity to vital structures, and the potential overlap of physiological and pathological radiotracer uptake patterns make it difficult to accurately differentiate benign from metastatic LNs [29]. Moreover, several LN factors, including size and necrosis, that could lead to low metabolic activity contribute to the high incidence of false-negative findings on PET/CT [30].…”
Section: Discussionmentioning
confidence: 99%
“…In routine practice, the analysis of 18 F-FDG PET/CT images of the head and neck region is challenging [27,28]. The intricate anatomical composition of the head and neck region, its proximity to vital structures, and the potential overlap of physiological and pathological radiotracer uptake patterns make it difficult to accurately differentiate benign from metastatic LNs [29]. Moreover, several LN factors, including size and necrosis, that could lead to low metabolic activity contribute to the high incidence of false-negative findings on PET/CT [30].…”
Section: Discussionmentioning
confidence: 99%
“…En la práctica clínica, según las guías actuales de la NCCN, en la valoración inicial de los CCC, la FDG PET/TC se reserva para los estadios avanzados (T3-4 o N1) debido a la alta probabilidad de encontrar enfermedad locorregional o diseminada en el momento del diagnóstico, que puede provocar cambios significativos en la actitud terapéutica, como evitar la realización de cirugías agresivas (6,19).…”
Section: Estadificaciónunclassified
“…However, it is always difficult for patients with recurrence and metastasis to obtain tumor tissues. 2-Deoxy-2-[ 18 F] fluoro-D-glucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) is acknowledged as an important non-invasive whole-body molecular imaging modality for evaluation of various tumors [ 7 , 8 , 9 , 10 , 11 , 12 ]. It has been reported that 18 F-FDG PET/CT could be used to predict multiple molecular phenotypes for malignant tumors, for instance, HER2 expression in gastric cancer [ 13 ], EGFR mutations and positive ALK expression in NSCLC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%